FENOMENA STANDAR KECANTIKAN DI TIKTOK SERTA RESPONS KRITIS MAHASISWA PENDIDIKAN SOSIOLOGI UNIVERSITAS SULTAN AGENG TIRTAYASA - Siti Rahmah Indriyani; Stevany Afrizal (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
The phenomenon of beauty standards on TikTok, such as fair skin, smooth faces, and ideal bodies, cannot be separated from the role of algorithms that continuously display content with certain beauty images. This study aims to describe how Sociology Education students at Sultan Ageng Tirtayasa University, class of 2023, assess these beauty standards and how they respond to them whether by accepting, rejecting, or criticizing them from a sociological perspective. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews with five students, supplemented by observation and documentation. The results show that most students view beauty standards on TikTok as a social construct that is not entirely realistic and tends to be shaped by digital media. The students' responses to this phenomenon also varied, ranging from selective acceptance, rejection of the pressure of beauty standards, to being critical in shaping their identity. This phenomenon can be understood through Berger and Luckmann's social construction theory, which explains the processes of externalization, objectification, and internalization in the formation of social meaning.